Peculiarities of face identification - Vanagaitė, Kristina; Valickas, Gintautas (Psichologija, 2002)
The article deals with different aspects of face identification. With the help of computer-based program, we have created two male standard-faces, which had to be remembered by the research participants. We have composed 5 stimuli-faces for each standard-face by changing corresponding face elements. In the present study research participants (n=70) were asked to ascertain whether the stimuli-faces differ from the standard-face by certain face elements. On the basis of the research results we can affirm, that not all face elements are identified equally exactly and in the same time (from the photograph). Hair and eyes were identified in the shortest time and the most exactly. Besides, women in contrast with men recognize changed elements of man’s standard-face more exactly.